Prognostic Implications of Biventricular Global Longitudinal Strain in Patients With Severe Isolated Tricuspid Regurgitation - Kim, Dae-Young; Seo, Jiwon; Cho, Iksung; Lee, Seung Hyun; Lee, Sak; Hong, Geu-Ru; Ha, Jong-Won; Shim, Chi Young (Frontiers in Cardiovascular Medicine, 2022)
Background Isolated TV surgery can be performed in patients with symptoms caused by severe isolated tricuspid regurgitation (TR), preferably before the onset of significant right ventricular (RV) dysfunction. In patients with severe TR, intrinsic RV dysfunction tends to be masked and promotes left ventricular (LV) mechanical dysfunction. This study investigated the prognostic implications of biventricular global longitudinal strain (GLS) in patients receiving isolated tricuspid valve (TV) surgery. Methods Among 1,670 patients who underwent TV surgery between January 2000 and December 2020, 111 patients with severe isolated TR who underwent echocardiography before and after TV surgery were analyzed. We assessed LV, RV, and biventricular GLS using speckle tracking echocardiography. Biventricular GLS was defined as the sum of LV-GLS and RV free-wall strain. The primary outcomes were cardiovascular death, heart failure hospitalization, re-done TV surgery, and heart transplantation. Results During 3.9 ± 3.8 years of follow-up after the postoperative echocardiography, 24 (21.6%) patients experienced a primary outcome. Those patients had more comorbidities and more impaired preoperative RV-GLS and biventricular GLS than those who did not experience a primary outcome, although the two groups did not differ in preoperative LV-GLS. Patients with a primary outcome also showed significantly impaired postoperative RV-GLS, biventricular GLS, and LV-GLS compared those without a primary outcome. In multivariate analyses, both pre- and postoperatively assessed RV-GLS [preoperative; hazard ratio (HR) 0.86, confidence interval (CI) 0.79–0.93, p < 0.001, postoperative; HR 0.89, CI 0.82–0.96, p = 0.004] and biventricular GLS [preoperative; HR 0.96, CI 0.91–1.00, p = 0.048, postoperative; HR 0.94, CI 0.89–0.99, p = 0.023] were independently associated with the primary outcomes. Conclusion In patients with severe isolated TR undergoing TV surgery, the absolute value of RV-GLS under 17.2% is closely associated with a poor prognosis, and that of biventricular GLS under 34.0%, mainly depending on the RV-GLS, is related to the poor prognosis. Further prospective multicenter studies are warranted to establish the risk stratification of isolated TV surgery.